Upaya meningkatkan kompetensi guru dalam menyusun rencana pelaksanaan pembelajaran (RPP) melalui Work Shop dan bimbingan berkelanjutan di SDN 01 Lunang Kecamatan Lunang - Amrizul Amrizul (JPGI (Jurnal Penelitian Guru Indonesia), 2018)
The teachers of  SDN 01 Lunang has compiled RPP in accordance with basic competence (KD) subjects. However, there are still various shortcomings concerning preparation before the preparation of RPP, in the preparation of RPP, as well as in the implementation of learning. This research is based on the condition of the field were not all teachers of SDN 01 Lunang, especially those with honorary status, have the opportunity to attend the work shop or KTSP training, the KKG activity rarely discusses the lesson plan. Such conditions make teachers' perceptions of SDN 01 Lunang regarding the RPP they need to prepare before implementing lessons in classrooms, studios or other places of learning to be diverse and less comprehensive. This research is in the form of School Action Research, using the descriptive method. Data collection technique in this research is interview, observation, and discussion. The subjects of this study were teachers of SDN 01 Lunang, which amounted to 12 teachers. The result of research shows that there is an increase of teacher competence in preparing RPP.